FAKTOR DETERMINAN PENGETAHUAN, SIKAP, DAN PRAKTIK PASIEN DIABETES TERHADAP DIABETIK NEUROPATI, NEFROPATI DAN RETINOPATI - Ns Ismail S.Kep, M.Kes; Muhammad Basri; Sukriyadi Sukriyadi; Nasrullah Nasrullah; simunati simunati; nuraeni Nuraeni; Suparta Mahmuddin (Media Keperawatan:Politeknik Kesehatan Makassar, 2023)
Background: The contribution of potential knowledge, attitudes and practices related to microvascular complications of diabetes is a determinant factor to consider. Objectives: Research is projected to determine the prevalence of DM characteristics and microrvascular complications, the potential for KAP to complications, health-seeking behaviors, follow-up problems, stigma and sources of information. Method: The cross-sectional approach is the main choice of research design in this study. This study took place in February – November 2021 which succeeded in recruiting the research subjects of 375 patients in Makassar City with diabetes observed. Results: The characteristics of DM type in this study included 3 types (DM type 1, DM type 2 and gestational DM), which were dominated by DM type 2, 310 (82.23%), followed by DM type 1, 59 (15.65%) and the smallest was Gestational diabetes 6 (2.12%) from 375 patients. The correlation of significance between quality of life and DM was shown to have positive values in aspects of knowledge and practice (r = 0.1; p = 0.002 ; r = 0.3;  p=0.02), only the negative attitude aspect (r=-0.2;  p=0.002). The correlation of knowledge of DM patients is directly proportional to the absence of: microvascular complications of diabetes (5.10 ± 2.64 versus 1.12 ± 0.33;  P<0.001), coronary artery disease (3.69 ± 2.65 versus 2.08 ± 2.25;  P<0.001), dyslipidemia (2.85 ± 2.58 versus 1.89 ± 2.07; p<0.001), hypertension (2.86 ± 2.62 versus 1.98 ± 2.11; p<0.001). Conclusion: This study provides invaluable information in helping to design and develop a supporting program model to educate and train DM patients and health workers professionally, especially in health service facilities in Makassar City in order to minimize the development of microvascular complications of diabetes